The Effect of Physical Fitness and Self-Confidence on the Martial Arts of Pencak Silat - Dea Siti Nurjanah; Herman Subarjah; Indra Safari (JUARA : Jurnal Olahraga, 2022)
This study aimed to determine the effect of physical fitness and self-confidence on the martial art of Pencak Silat. The research method used is the ex post facto method. The research design describes the relationship or influence between a variable and other variables. The population is students who take extracurricular Pencak silat at SMPN 1 Parongpong, with a sample of 30 people. The test instrument for martial arts skills is the Pencak silat regarding single empty-handed moves; physical fitness tests are TKJI for the age range of 13-15 years and a self-confidence questionnaire. Based on the processing and analysis, they use the technical correlation analysis but were previously tested for normality, regression and linearity. The hypotheses of this study are 1) With a positive effect, the higher the physical fitness, the better the martial arts skills of Pencak silat. There is an influence of physical fitness on the martial art of Pencak silat by 55.91%, 2) With a positive impact, the higher the self-confidence, the better the martial arts skills of Pencak silat. There is an influence of self-confidence on the martial art of Pencak silat by 27.29%, and 3) Of the two variables, the effect is excellent on these skills. So there is an influence between physical fitness and self-confidence on the martial art of Pencak silat by 235.26%.